Sistem Pemerintahan Jepang Pada Muslim Jambi Syu Tahun 1942-1945 - Mina Zahara; Agus Fiadi (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2022)
This research is motivated by the author's observations on Japanese heritage in Jambi. Whether in the form of documents, objects and buildings. Meanwhile, the information regarding the Japanese occupation in Jambi is still insufficient and complete. Therefore the authors are interested in raising the title Reconstruction of the Dynamics of the Japanese Occupation Government in Jambi Syu. 1942-1945 AD. The research objective was to describe the state of Jambi prior to the Japanese occupation. Then describe the history of the Japanese entry in Jambi. Next, he describes the government system that was applied during the Japanese occupation in Jambi. This type of research is literature research using descriptive analytical methods with a historical approach using historical method work steps, the researcher will try to describe and tell what the author found in a thesis entitled Reconstruction of the Dynamics of Japanese Occupation Government in Jambi Syu. 1942-1945 AD. The results of this study indicate that before Japan conquered the Jambi residency, Japan first carried out propaganda in various aspects. Only then did Japan conquer. The government system used by Japan is different from the government system applied during the Dutch administration. the government system applied is a militaristic government sistem. This change has had a profound impact on the lives of the people of Jambi. Although using a different government system, the government structure used follows the old structure with changes in the pronunciation of each position into Japanese.